2004
DOI: 10.1128/mcb.24.9.3794-3803.2004
|View full text |Cite
|
Sign up to set email alerts
|

Insertion of the βGeo Promoter Trap into the Fem1c Gene of ROSA3 Mice

Abstract: ROSA3 mice were developed by retroviral insertion of the ␤Geo gene trap vector. Adult ROSA3 mice exhibit widespread expression of the trap gene in epithelial cells found in most organs. In the central nervous system the highest expression of ␤Geo is found in CA1 pyramidal cells of the hippocampus, Purkinje cells of the cerebellum, and ganglion cells of the retina. Characterization of the genomic insertion site for ␤Geo in ROSA3 mice shows that the trap vector is located in the first intron of Fem1c, a gene hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 26 publications
(23 reference statements)
2
12
0
Order By: Relevance
“…For these experiments, we used Fem1c Rosa3 (R3) mice, which contain the βGeo promoter trap reporter in the first intron of the Fem1c gene. Previously, we showed that mice express βGEO in an RGC-specific manner [12]. Additionally, we have observed a 75% decrease in βGEO total protein and enzyme activity [12], and a 50% decrease in Fem1c transcript levels, by 5 days post ONC (Figure 8A, B).…”
Section: Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…For these experiments, we used Fem1c Rosa3 (R3) mice, which contain the βGeo promoter trap reporter in the first intron of the Fem1c gene. Previously, we showed that mice express βGEO in an RGC-specific manner [12]. Additionally, we have observed a 75% decrease in βGEO total protein and enzyme activity [12], and a 50% decrease in Fem1c transcript levels, by 5 days post ONC (Figure 8A, B).…”
Section: Resultssupporting
confidence: 51%
“…Previously, we showed that mice express βGEO in an RGC-specific manner [12]. Additionally, we have observed a 75% decrease in βGEO total protein and enzyme activity [12], and a 50% decrease in Fem1c transcript levels, by 5 days post ONC (Figure 8A, B). Thus, the R3 reporter allows for the rapid detection and quantification of changes in RGC gene expression.…”
Section: Resultssupporting
confidence: 51%
“…53,54 Mice were anesthetized with an intraperitoneal injection of ketamine (6 mg/ mL) and xylazine (0.4 mg/mL), and the left eye was numbed with one drop of Alcain (Alcon Laboratories, Ft. Worth, TX) prior to both the injection and ON crush. Twenty-four hours prior to crush, the sclera of the left eye of each mouse was punctured with a 30-gauge needle, and 2 lL of a 10% solution of supplement (FBS, G5, N2, EN2, or EN2 without HC) diluted in balanced saline solution was injected through a glass micropipet inserted into the vitreous.…”
Section: On Crush Procedures and Counting Of Surviving Rgcsmentioning
confidence: 99%
“…Humans have a ubiquitously expressed 6.2-and 3.8-kb mRNA and a testis-specific 2.8-kb transcript. Schlamp et al (2004) reported a slight non-significant increase in the number of female pups in a mouse line with reduced expression of Fem1c, caused by insertion of the βGeo gene trap vector in the first intron of Fem1c gene, and concluded that the gene had no known effect on sexual development or fertility.…”
Section: Introductionmentioning
confidence: 99%